The role of the NMDA receptor in alcohol relapse: a pharmacological mapping study using the alcohol deprivation effect - Vengeliene, Valentina; Bachteler, Daniel; Danysz, Wojciech; Spanagel, Rainer (Neuropharmacology, 2005)
Modulators of glutamate receptors especially of the N-methyl-d-aspartate receptors (NMDARs) have recently been suggested as putative pharmacotherapeutic agents in the treatment of alcohol relapse. However, at present it is not clear, which binding and modulatory sites of the NMDAR are involved in relapse behavior. We, therefore, performed a pharmacological mapping study in long-term alcohol drinking rats using the alcohol deprivation effect (ADE) as a model for relapse behavior. In a comprehensive fashion, we studied dose-response curves, employing the following selective pharmacological agents: the NMDAR competitive antagonist CGP37849, the glycine binding site antagonist L-701.324, the NR2B subunit selective antagonist ifenprodil, which acts at the polyamine binding site, the NMDAR channel blocker neramexane, and ethanol, which acts as a functional antagonist at the NMDAR. Our data show that the animals' alcohol consumption inversely correlates with the dose of ethanol administered intraperitoneally. This indicates that under the present experimental conditions alcohol intake during an ADE is an entirely pharmacologically driven behavior that is not under the control of other factors such as taste or novelty of alcohol re-exposure. The effects of the administration of the aforementioned compounds were comparable to those of ethanol, suggesting a similar pharmacological impact on relapse behavior. Repeated administration of both competitive and uncompetitive NMDAR antagonist dose-dependently suppressed alcohol consumption during ADE. In addition, ifenprodil and L-701.324 dose-dependently reduced the expression of an ADE as well. In summary, the results suggest that an inhibition of NMDAR function in general, rather than a particular interference with a specific binding site of this receptor, is sufficient for the reduction of relapse behavior.
Gesehen am 22.10.2020